Comparison of caffeine-induced locomotor activity between adolescent and adult rats - Marin, Marcelo Tadeu [UNESP]; Zancheta, Roberta [UNESP]; Paro, Ana H. [UNESP]; Possi, Ana P. M. [UNESP]; Cruz, Fabio C. [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Elsevier B.V., 2011)
Caffeine is the psychostimulant drug most consumed in the world. This drug is present in food, beverages and medicines marketed for individuals of all ages. In spite of this, caffeine effects on adolescents are poorly understood. The aim of this study was to evaluate the differences on caffeine-induced locomotor stimulant or depressant effects in adolescent and adult rats. Adolescent (37-40 days old) or adult (70-74 days old) Wistar rats were tested for stimulant and depressant caffeine effects in two different experiments. The first was designed to evaluate the locomotor effect of caffeine in habituated rats. To this end, rats were previously habituated to test environment and had their locomotor activity registered following i.p. injections of vehicle or caffeine (3, 10, 30, 60 or 120 mg/kg). In the second experiment adolescent or adult rats were not habituated to the test environment and their locomotor activity was registered following i.p. injections of vehicle or caffeine (30, 60 or 120 mg/kg). In both experiments caffeine-induced a biphasic effect, with stimulation in small to moderate drug doses and no effect or locomotor depression in higher caffeine doses. Moreover, caffeine-induced locomotor stimulation was higher in adolescent than adult rats. Also, locomotor depression was only revealed in adult rats non-habituated to the test environment. These results suggest that adult and adolescent respond differently to caffeine indicating the need of more studies on the effects of caffeine in animals' models of adolescence. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Caffeine; Adolescence; Locomotor activity; Psychostimulant